Gênero ou sexualidade?: (re) produção das identidades homoeróticas masculinas no cinema de massa - Nunes, Kenia Almeida (2013)
Homosexuality has been gaining strength in Cinema from the late twentieth century, when there is a dissemination of freedoms around the peripheral or marginal sexualities. Based on this assumption, it was formulated in the dissertation work, an analysis of the relationship between Cinema and Sexuality in order to understand, describe, reflect and analyze possible changes around the performative behaviors of male homosexual from the introduction of them in film production, arising from the mass culture industry. These productions are located in three different decades. In this case, the Cinema has not only the reproductive character of realities, but also a producing agent and consolidating them. The methodology applied was discourse analysis of three film works, namely La Cage aux Folles (1978), In & Out (1997) and Boat Trip (2002). The image, research object of this work, is developed by a mass culture that will produce mass identities which is characterized by crystallization of clichés around the gay world